2004
DOI: 10.1086/382285
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms in Finnish Families: Confirmation of Linkage and Refinement of the Interval to Chromosome 19q13.3

Abstract: We recently reported a two-stage genomewide screen of 48 sib pairs affected with intracranial aneurysms (IAs) that revealed suggestive linkage to chromosome 19q13, with a LOD score of 2.58. The region supporting linkage spanned approximately 22 cM. Here, we report a follow-up study of the locus at 19q13, with a sample size expanded to 139 affected sib pairs, along with 83 other affected relative pairs (222 affected relative pairs in total). Suggestive linkage was observed in both independent sample sets, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Collectively, candidate regions that have to date been replicated in Ͼ1 study include 7q11 (Onda et al and Farnham et al) and 19q13 (Olson et al and Van Der Voet et al). [3][4][5]7 The regions of 17cen (Onda et al 3 ) and Xp22 (Olson et al 4 ) are extended in the present study. Such concordant regions should be considered as high-priority loci and provide promising scaffolds for future studies to identify the exact genetic mechanisms for IA.…”
Section: Discussion Linkage Analysissupporting
confidence: 66%
See 2 more Smart Citations
“…Collectively, candidate regions that have to date been replicated in Ͼ1 study include 7q11 (Onda et al and Farnham et al) and 19q13 (Olson et al and Van Der Voet et al). [3][4][5]7 The regions of 17cen (Onda et al 3 ) and Xp22 (Olson et al 4 ) are extended in the present study. Such concordant regions should be considered as high-priority loci and provide promising scaffolds for future studies to identify the exact genetic mechanisms for IA.…”
Section: Discussion Linkage Analysissupporting
confidence: 66%
“…4 The region on chromosome 19q13 was also replicated by another Finish study. 7 The region on chromosome 19q13 may thus not be specific to Finnish population. Collectively, candidate regions that have to date been replicated in Ͼ1 study include 7q11 (Onda et al and Farnham et al) and 19q13 (Olson et al and Van Der Voet et al).…”
Section: Discussion Linkage Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…So far, different genome-wide linkage studies have identified several loci [44], but only four (p4.-p6., 7q, 9q. and Xp22) have been replicated in different populations [75,246,259,28,284,45,420,49]. Knowledge on the genetic determinants may provide insight into the development of aneurysms, and thereby give clues on how to stop aneurysm formation.…”
Section: Genetics Of Intracranial Aneurysmsmentioning
confidence: 99%
“…Up to 20% of patients with IA have a positive family history [1][2][3] and there is up to a 7-fold increased risk of IA rupture among first-degree relatives compared with second-degree relatives. 4 Although many genetic loci have been linked to familial IA, [5][6][7][8][9][10][11][12][13][14][15] no single disease-causing gene variant has been identified. In this study, we performed genomewide linkage analysis on a single family to identify an IA susceptibility locus.…”
mentioning
confidence: 99%